2015
DOI: 10.1002/smi.2667
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Engagement as Mediators in the Relationship between Work Characteristics and Turnover Intentions across Two Ibero-American Nations

Abstract: This study examines the mediating effects of burnout and engagement on the relationships between work characteristics (work overload and social support) and turnover intentions in the nursing community of two Ibero-American countries within the job demands-resources model. The sample consists of 316 registered nurses employed in Uruguay and 502 employed in Spain. We used multiple structural equation modelling analyses. The proposed model fit the data for both nursing samples. Burnout was found to fully mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 58 publications
(95 reference statements)
1
41
0
2
Order By: Relevance
“…In this sense, regarding burnout, Gabel Shemueli, Dolan, Suárez Ceretti, and Nuñez del Prado (2016) found that it fully mediated the relationship between work overload and TI of nurses from Spain and Uruguay. In a similar vein, Amponsah-Tawiah, Annor, and Arthur (2016) observed, in a multi-occupational Ghanaian sample, that commuting stress was indirectly related to job satisfaction and TI via burnout.…”
Section: Literature Review and Hypothesesmentioning
confidence: 85%
“…In this sense, regarding burnout, Gabel Shemueli, Dolan, Suárez Ceretti, and Nuñez del Prado (2016) found that it fully mediated the relationship between work overload and TI of nurses from Spain and Uruguay. In a similar vein, Amponsah-Tawiah, Annor, and Arthur (2016) observed, in a multi-occupational Ghanaian sample, that commuting stress was indirectly related to job satisfaction and TI via burnout.…”
Section: Literature Review and Hypothesesmentioning
confidence: 85%
“…The study of burnout in healthcare professionals is important as it has impacts at the level of the individual provider [3][4][5], the patient [6][7][8][9], and the organization [5,[10][11][12]. As nurses make up the largest group of healthcare professionals, there have been a number of studies that have explored contributing factors [13] and interventions for their burnout [14].…”
mentioning
confidence: 99%
“…Burnout, and its effects on staffing procedures and performance management, has been studied for several decades. Few topics in the realm of organizational research are of more importance; burnout has been linked to decreased job satisfaction and job performance, and is thought to be a driver of negative outcomes for employees, including increased absences from work (Jourdain & Chênevert, ), intentions to quit (Shemueli, Dolan, Ceretti, & Prado, ) and both mental and physical health issues (Bakker & Costa, ; Glaser & Kiecolt‐Glaser, ; Ross‐Adjie, Leslie, & Gillman, ).…”
Section: Overviewmentioning
confidence: 99%
“…Fortunately, nursing management may have the ability to prevent or reduce burnout by influencing its antecedent factors. The relationship between stress, burnout, and turnover is outlined by the job demands‐resources model, or JD‐R model (Shemueli et al., ). Shemueli and colleagues presented and tested this model, which links job demands (e.g., workload, psychological strain, and other individual costs of working), and job resources (e.g., physical and social assets, “tools,” and mechanisms that help individuals deal with job demands).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation